Modern techniques for financial transactions and their effects on currency : general and national reports : XIVth International Congress of Comparative Law, Athens, 31 July-7 August 1994 /: general and national reports : XIVth International Congress of Comparative Law, Athens, 31 July-7 August 1994. (1995) - Unknown
No abstract available